2018
DOI: 10.1177/0361684318812475
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders in the Workplace: A Qualitative Investigation of Women’s Experiences

Abstract: Though employment is typically associated with positive mental health outcomes for individuals with disabilities, the ubiquity of stress and stigma at work may complicate the relation between work and well-being for women with eating disorders (EDs). To date, however, the experiences of women with EDs in the workplace have not been examined. By utilizing a qualitative methodology to form an initial framework for the examination of EDs in the workplace, we address this gap in the literature. Seventy adult women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 104 publications
(100 reference statements)
1
23
0
Order By: Relevance
“…Providing additional data which highlights objective strengths such as high workplace participation may help to de-stigmatize living with an eating disorder and promote inclusivity [ 43 ]. Increased recognition of high workplace participation in AN may be used to promote more specific investigation of work as a potential recovery factor, and to provide focused support for the everyday challenges posed by the workplace [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Providing additional data which highlights objective strengths such as high workplace participation may help to de-stigmatize living with an eating disorder and promote inclusivity [ 43 ]. Increased recognition of high workplace participation in AN may be used to promote more specific investigation of work as a potential recovery factor, and to provide focused support for the everyday challenges posed by the workplace [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, rigorous qualitative methods can provide a foundation for gathering information on employees’ lived experiences with mental illness, including the ways in which it disrupts, modifies, or enhances their job. Recent explorations of specific mental illnesses, such as depression (Follmer & Jones, 2017a), eating disorders (Siegel & Sawyer, 2017), and autism (Johnson & Joshi, 2016), have been useful in revealing specific strategies that individuals and organizations can use to better manage these conditions.…”
Section: Mental Illness In the Workplace: A Future Research Agendamentioning
confidence: 99%
“…There are very few studies investigating the role of the workplace for eating disorder recovery. A qualitative study by Siegel and Sawyer [7] showed that the participants placed great importance on workplace factors, such as supportive managers and colleagues, when it came to either reach or stay in recovery. Previous research has also shown that the workplace is an important arena for recovery from other types of mental ill-health, such as depression and anxiety [36].…”
Section: Discussionmentioning
confidence: 99%
“…The workplace has, however, been shown to be a potentially difficult site for symptom management for women with eating disorders. Certain workplace stressors such as leader intolerance, co-worker awareness, schedule conflicts, and health-focused workplaces moderate the type of strategy used for stress management, and the findings of Siegel and Sawyer [ 7 ] indicate that management techniques used may contribute to either relapses or recovery of the eating disorder.…”
Section: Introductionmentioning
confidence: 99%